2012
DOI: 10.1007/s13762-012-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive biomasses and antagonist bacteria for an eco-compatible control of Verticillium dahliae on nursery-grown olive plants

Abstract: Two organic amendments (OMW-M1 and OMW-M2), based on olive mill wastes (OMWs) subjected to advanced processes of aerobic static storage or composting, were tested for their suppressive activity against Verticillium dahliae, the causal agent of olive Verticillium wilt. OMW-M1 and OMW-M2 drastically inhibited the pathogen growth in vitro and then were further tested in suppressive pot experiments. The amendments, mixed at 15 % (v/v) with a nursery standard plant-growth matrix, were tested alone or in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…These results are in agreement with those obtained by Vitullo et al . (), who also demonstrated that the volatile compounds produced by OAs were effective in controlling V. dahliae on nursery‐grown olive plants. These results are relevant because antagonistic effect of OAs on mycelial growth development could be useful to prevent pathogen establishment/development in nursery substrates as well as in natural soils.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…These results are in agreement with those obtained by Vitullo et al . (), who also demonstrated that the volatile compounds produced by OAs were effective in controlling V. dahliae on nursery‐grown olive plants. These results are relevant because antagonistic effect of OAs on mycelial growth development could be useful to prevent pathogen establishment/development in nursery substrates as well as in natural soils.…”
Section: Discussionmentioning
confidence: 92%
“…However, the effect of OAs as a potential control tool against VW of olive was not studied again until recently, when Vitullo et al . () showed the effect of olive mill liquid wastes on nursery‐grown olive plants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations